Wealth Distribution and Class Reconstruction in the Context of Artificial Intelligence - Ting Chen; Zihan Tang (Journal of World Economy, 2025)
The rapid development of artificial intelligence technology is reshaping the global production system with unprecedented strength. In this process, the phenomena of imbalance in wealth distribution and class restructuring triggered by the technology have gradually exceeded the scope of explanation of traditional economics. In order to deeply understand this phenomenon, this paper adopts historical materialism as an analytic tool, aiming to reveal the deep mechanism of technological alienation in the era of artificial intelligence. It explores how the intelligence revolution has systematically reconfigured the labor value pattern, capital accumulation mode and social power structure, and these changes are profoundly affecting the logic of socioeconomic operation. On this basis, this paper further proposes a social governance path that conforms to the laws of technological civilization evolution, aiming at balancing technological development and social equity, ensuring that technological progress can benefit a wider range of social groups, and promoting the construction of a more harmonious and sustainable pattern of social development.